Pemidanaan bagi Pelaku Tindak Pidana Perkosaan terhadap Penyandang Disabilitas - A.A. Kompiang Dhipa Aditya; I Nyoman Gede Sugiartha; Ni Made Sukaryati Karma (Jurnal Konstruksi Hukum, 2020)
Persons with disabilities refer to people who have physical, intellectual, mental, or sensory deficiencies so that in living their lives they find hindrances, as an opposite to normal people. Oftentimes the persons with disabilities receive poor treatment in society, be it discriminatory treatment or criminal acts, one of which is rape. Unfortunately, criminal sanctions for perpetrators of rape against persons with disabilities in Indonesia have not been explicitly regulated. Grounded with this phenomenon, this study examines the legal protection for persons with disabilities as victims of the criminal act of rape and sanctions for the perpetrators of the said criminal acts. To achieve these goals, this study was conducted using a normative legal research method with a conceptual approach and a case approach. Legal protection for persons with disabilities is contained in Article 3 and Article 5 Paragraph (2) of Law Number 8 of 2016 which regulates the rights and legal protection for persons with disabilities as victims of criminal acts. Protection for the rape victims takes the form of restitution and rehabilitation assistance. Sanctions for the perpetrators of the criminal act of rape against persons with disabilities have not been regulated strictly. In the Criminal Code, the criminal acts of rape are regulated in general sphere that is in Articles 285, 286, 287, 288. Thus, the legal protection for persons with disabilities aims to safeguard and maintain the persons with disabilities from the criminal acts of rape. In the Cassation Decision Number 736K/PID/2013 PN Cn, the sanction for perpetrators of rape against persons with disabilities is the imposition of sanctions in the provisions of Article 285 of the Criminal Code.